Staurastrum volans var. fuquenense nov. var., an interesting desmid taxon in the phytoplankton of laguna fúquene (colombia) (1986)
Of Staurastrum volans W. and amp; G. S. West, previously only known from Africa, a variety fuquenense COESEL is newly described from laguna Fúquene in the Colombian Andes. Judging from the ecological data of the localities in Colombia and from those recorded from African habitats, Staurastrum volans may be characterized ecologically as a planktonic desmid species that is well adapted to neutral to somewhat alkaline, eutrophic and unstable habitats.